Factors associated with the scientific production of academics in the Faculty of Dentistry of the National University of San Marcos. Lima Peru. - Yuri Castro-Rodríguez; Yens Mendoza-Martiarena; Manuel Tello-Espejo; Claudia Piscoche-Rodríguez (Universidad de Concepción., 2019)
Publishing scientific articles allows for disseminating the results of a study and concludes the research process; such publication allows the academic to develop more research skills. Objective: To analyze the factors associated with the production of scientific articles in university professors. Material and Methods: Analytical cross-sectional study that collected the amount of articles published in the Scopus and SciELO databases by ordinary professors of the Faculty of Dentistry of the National University of San Marcos (Lima, Peru). Associated factors included: sex, teaching category, dedication time, academic degree, positions at other universities, professional experience and teaching courses related to scientific research. Results: 20.8% of academics presented at least one article published. Male sex (OR = 1.12, 95% CI: 1.04-2.49), working at one university only (OR = 1.39, 95% CI: 1.12-2.71), teaching courses related to research methodology (OR = 1.35, 95% CI: 1.05-4.27) and having more than 10 years' experience in university teaching (OR = 2.95, 95% CI: 2.1-8.97) were factors associated with greater scientific production. Conclusions: One fifth of ordinary professors presented scientific production in the databases Scopus and SciELO, with the main factors associated with a greater production of scientific articles being sex, course teaching, number of years in teaching and number of work-institutions.